Canadian Registry of Implantable Electronic Device Outcomes: Surveillance of the Riata Lead Under Advisory. (October 2016) - Parkash, Ratika; Thibault, Bernard; Mangat, Iqwal; Coutu, Benoit; Bennett, Matthew; Healey, Jeffrey; Verma, Atul; Philippon, Francois; Sandhu, Roopinder; Cameron, Douglas; Ayala-Paredes, Felix; Sterns, Laurence; et al.
Abstract : Background—: The Riata lead under advisory has posed a unique clinical scenario where inside-out abrasion results in externalization of conductor cables, with a higher risk of electrical failure. We developed a comprehensive registry to assist with clinical management of this lead. Methods and Results—: This Canadian registry reports the findings of 3763 (74.2% of all Riata leads in Canada) Riata leads under advisory, with a mean follow-up time of 8.9±1.5 years. The overall electrical failure rate was 5.2% at 8 years, with no difference between 7-French and 8-French lead models. Cable externalization was found to be more common in the 8-French model (12.3% versus 5.2%, P <0.0001) and was associated with a higher risk of electrical failure. Predictors of electrical lead failure included cable externalization, higher left ventricular ejection fraction, younger age, higher body mass index, and a passive fixation lead. One patient died due to electrical failure, a further 2 patients survived an event where the device failed to deliver high-voltage therapy. Major complications because of lead extraction were higher when compared with lead abandonment, no difference among lead model observed. Two deaths occurred as a consequence of lead extraction, in the context of an underlying infection. Conclusions—: The Riata lead under advisory has a steady electrical failure rate over time. There are identifiable predictors of lead failure that can assist with clinical decisions as to whether lead revision should be performed prophylactically.